What are the recommendations for returning athletes who have experienced long term COVID-19 symptoms?. (1st January 2021) - Lindsay, Rosie K.; Wilson, Jason J.; Trott, Mike; Olanrewaju, Olawale; Tully, Mark A.; López-Sánchez, Guillermo F.; Shin, Jae Il; Pizzol, Damiano; Allen, Peter; Butler, Laurie T.; Barnett, Yvonne; Smith, Lee
Abstract: Currently, there is limited research reporting the symptoms of long COVID among athletes, and the recommendations for athletes returning to competition/training who have experienced long COVID symptoms. Therefore, the aim of this systematic review is to synthesise the recommendations for returning athletes who have experienced long COVID symptoms. The protocol was registered in PROSPERO under CRD42021265939. Two authors searched the electronic databases PubMed, Embase, Scopus, the Cochrane Library, Web of Science, CINAHL, PsycINFO, and SPORTDiscus from August 2019-July 2021. Search terms included words related to "long COVID", "athlete" and "return". Data extraction was completed for each study by two independent investigators for: (1) first author name; (2) year of publication; (3) journal; (4) Definition of athlete (i.e. elite or non-elite) (5) Recommendations reported. A total of 220 records were found. Following title and abstract screening, 61 studies were eligible for full text screening. Overall, no studies, commentaries, editorials or reviews provided specific recommendations for "long COVID" defined as COVID-19 signs and symptoms lasting for over 4 weeks as a result of COVID-19 infection. In addition, we found no studies which reported symptoms of athletes suffering from long COVID. Despite the lack of evidence, we did find eight separate professional recommendations for managing "long-term effects" and "ongoing" or "prolonged" symptoms and COVID-19 complications among athletes. Practitioners should be aware of both mental and physical symptoms of long COVID, and additional considerations may be required for athletes who have undergone intensive care. The present review provides a list of recommendations based on existing literature that may be followed and implemented for returning athletes. Key Messages: Further research, including longitudinal research of athletes who have tested positive for COVID-19, is required to develop evidenced-based guidelines for athletes with ongoing COVID-19 symptoms. Prior to returning to play after COVID-19 infection, a thorough medical history, physical and psychological examination should be conducted by a medical professional. Athletes should continue to monitor and record their own physical and psychological markers of health.